Sex differences in the evaluation of proteinuria using the urine dipstick test - Kojima, Chiari; Umemura, Hiroshi; Shimosawa, Tatsuo; Nakayama, Tomohiro (Frontiers in Medicine, 2023)
Background: The urine protein dipstick test is widely used, but false-positive and false-negative results may occur. This study aimed to compare the urine protein dipstick test with a urine protein quantification method. Methods: The data were extracted using the Abbott Diagnostic Support System, which analyzes the inspection results using multiple parameters. This study included 41,058 specimens tested using the urine dipstick test and protein creatinine ratio from patients aged ≥ 18 years. The proteinuria creatinine ratio was classified according to the Kidney Disease Outcomes Quality Initiative guidelines. Results: Urine protein on the dipstick test was negative in 15,548 samples (37.9%), trace in 6,422 samples (15.6%), and ≥ 1+ in 19,088 samples (46.5%). Among the trace proteinuria samples, A1 (< 0.15 g/gCr), A2 (0.15–0.49 g/gCr), and A3 (≥ 0.5 g/gCr) category proteinuria accounted for 31.2%, 44.8%, and 24.0% of samples, respectively. All trace proteinuria specimens with a specific gravity of < 1.010 were classified as A2 and A3 category proteinuria. In the trace proteinuria cases, women had a lower specific gravity and a higher percentage of A2 or A3 category proteinuria than men. The sensitivity in the “dipstick proteinuria” ≥ trace” group was higher than that in the “dipstick proteinuria ≥ 1+” group within the lower specific gravity group. The sensitivity in the “dipstick proteinuria ≥ 1+” group was higher for men than for women, and the sensitivity in the “dipstick proteinuria ≥ trace” group was higher than that in the “dipstick proteinuria ≥ 1+” group for women. Conclusion: Pathological proteinuria assessment requires caution; this study suggests that evaluating the specific gravity of urine specimens with trace proteinuria is essential. Particularly for women, the sensitivity of the urine dipstick test is low, and caution is needed even with trace specimens.